A Study of Green Marketing Tools Influences on Green Cosmetic Product Purchasing In Malaysia - Khoh, Cindy (2012)
The awareness of green issue advocates the popularity of green product consumption, including the green cosmetic product. In Malaysia, the market for green cosmetic product still immature but it has started becomes vogue in Malaysia cosmetic industry. In view of the theory of planned behavior, this study provides a deep insight in regard of the influence of green marketing tools on the consumer purchasing behavior on green cosmetic product. The result of this study showed the green marketing tools started demonstrate its prominence in accordance to the Malaysia’s current market trend. The model showed that three of the green marketing tools, which are environmental advertisement, eco-label and eco-brand, are significantly influences consumer’s purchase behavior on green cosmetic product. It is expecting that this study can contributed assistance to the future practices that will be apply for the green cosmetic market in Malaysia.